Dataset containing Features from DNS Tunneling Samples stored in JSON files - Irvin Homem; Panagiotis Papapetrou (Stockholm University, 2016)
Data set containing features extracted from 211 DNS Tunneling packet captures. The packet capture samples are classified by the protocols tunneled within the DNS tunnel. The features are stored in json files for each packet capture. The features in each file include the IP Packet Length, the DNS Query Name Length and the DNS Query Name entropy. In this "slightly unclean" version of the feature set the DNS Query Name field values are also present, but are not actually necessary.

This feature set may be used to perform machine learning techniques on DNS Tunneling traffic to discover new insights without necessarily having to reconstruct and analyze the equivalent full packet captures.
Keywords: 80303 Computer System Security; 80503 Networking and Communications; 80109 Pattern Recognition and Data Mining; Computer Sciences; Datavetenskap (datalogi)